Immune check-point in glioblastoma multiforme. (June 2019) - De Felice, F.; Pranno, N.; Marampon, F.; Musio, D.; Salducci, M.; Polimeni, A.; Tombolini, V.
Highlights: The role of immune check-point inhibitors is being tested in glioblastoma multiforme (GBM). This is the largest updated analysis of preclinical and clinical trials in GBM. This analysis suggests that immune check-point inhibitors could influence outcomes in GBM. Abstract: Glioblastoma multiforme (GBM) represents one of the main frequent and aggressive primary brain neoplasms among adults worldwide. Despite a first-line multimodal treatment, including radical surgery and adjuvant radiation therapy with concomitant temozolomide-based chemotherapy, GBM prognosis continues to be unfavourable. During this decade, different research groups have explored immune check-point inhibitors role in order to improve response to therapy and subsequently prolong survival rate. The aim of this review was to analyze published literature to support immune check-point inhibitors use in the management of patients with GBM diagnosis. The hope was to help physicians for better decision-making.